Histomorphological Analysis of Skin Biopsies in Patients with Autoimmune Disorders: A Study from Pakistan - Bano, Sara; Beenish, Huma; Imran, Shazia; Khan, Waseem; Haroon, Arifa; Bashir, Saima (Journal of Neonatal Surgery, 2025)
Background: Autoimmune disorders frequently manifest with cutaneous involvement, and skin biopsy remains a valuable diagnostic tool for identifying characteristic histopathological features. Limited data exist from Pakistan regarding the histomorphological spectrum of skin lesions in autoimmune diseases. Objective: To analyze the histomorphological patterns of skin biopsies in patients with autoimmune disorders and to identify independent predictors of severe histopathological changes. Methodology: This cross-sectional study was conducted in the Rawalpindi Medical University for 1 year from June, 2024 to June, 2025. A total of 385 patients with clinically suspected autoimmune skin disorders were enrolled using consecutive sampling. Biopsies were processed and examined for histopathological features, including interface dermatitis, basal cell vacuolization, perivascular inflammation, and dermal fibrosis. Data were analyzed using SPSS version 25. Logistic regression was applied to determine independent predictors of severe histopathological features, adjusting for demographic and clinical factors. A p-value <0.05 was considered statistically significant. Results: Interface dermatitis (65.8%), basal cell vacuolization (52.5%), and perivascular inflammation (48.3%) were the most common findings. Logistic regression identified perivascular inflammation (OR: 2.45, 95% CI: 1.12–5.36, p=0.021) and basal cell degeneration (OR: 2.10, 95% CI: 1.05–4.19, p=0.033) as independent predictors of severe disease. Conclusion: The study underscores the diagnostic value of skin biopsy in autoimmune disorders, with specific histopathological features serving as markers of disease severity. These findings can support timely diagnosis and guide clinical management strategies.